The Hash Idea for Blockchain Security - Sinthuja, U. (INFOCOMP Journal of Computer Science, 2019)
Blockchain is gaining traction and can be termed as one of the furthermost prevalent topics nowadays. Although critics question about its scalability, security, and sustainability, it has already transformed many individuals’ lifestyle in some areas due to its inordinate influence on industries and businesses. Granting that the features of blockchain technology guarantee more reliable and expedient services, it is important to consider the security and privacy issues and challenges behind the innovative technology. In this paper hash function is discussed with algorithm to increase the security level.